Conventional follicular-phase ovarian stimulation vs. luteal-phase stimulation in suboptimal responders: a randomized controlled trial - Jorge Suñol, M.D; Juan Carlos Castillo, M.D., Ph.D; José Antonio Ortiz, M.Sc., Ph.D; Jorge Ten, M.Sc. Ph.D; Ana Fuentes, M.D; Belén Moliner, M.D., Ph.D; María Martínez, M.D; Joaquín Llácer, M.D., Ph.D; Jaime Guerrero, M.Sc. Ph.D; Ana Pitas, M.Sc. Ph.D; Andrea Bernabeu, M.D., Ph.D; Rafael Bernabeu, M.D., Ph.D (Elsevier, 2023)
Objective: To compare the oocyte yield between follicular-phase stimulation (FPS) and luteal-phase stimulation (LPS) in suboptimal responders. Design: Prospective, randomized, crossover clinical trial. Patient(s): Forty-one patients with infertility according to the POSEIDON (Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number) criteria (1b/2b). Intervention(s): Crossover study on 2 assigned ovarian stimulations that started randomly in the follicular or luteal phase. The in vitro fertilization cycles were not consecutive but separated in time (45 days to 6 months). The random crossover design ensured that all subjects received the first treatment by chance. Main Outcome Measure(s): The primary objective was the number of cumulus-oocyte complexes retrieved in each cycle. Secondary objectives were number of metaphase II and fertilized oocytes, additional doses of recombinant follicle-stimulating hormone, and the duration of ovarian stimulation (days). Result(s): The mean number of cumulus-oocyte complexes retrieved was similar between the FPS and LPS groups (7.5 ± 4.6 vs. 7.0 ± 4.1; 95% confidence interval [CI] for the mean, 5.8-8.7 vs. 5.6-8.3, respectively; the difference between means, −0.5; 95% CI, −1.8 to +1.5). Similarly, the mean number of metaphase II oocytes retrieved was not different between the FPS and LPS groups (5.4 ± 3.6 vs. 5.2 ± 2.8; 95% CI for the mean, 4.2-6.5 vs. 4.3-6.1, respectively; the difference between means, −0.2; 95% CI, −1.2 to +1.1). Moreover, the secondary objectives were similar between FPS and LPS groups. Conclusion(s): In this study, the oocyte yield in LPS did not increase in suboptimal responders compared with that in FPS when the onset of LPS was separated in time from FPS. Clinical Trial Registration Number: NCT039393990 https://beta.clinicaltrials.gov/study/NCT03939390.